APPLICATION OF SKIMMING READING TECHNIQUES TO INCREASED READING MOTIVATION IN STUDENTS IN E-LEARNING - ince muaggil (Universitas Sembilanbelas November Kolaka, 2022)
The purpose of creating this article is to examine whether the application of skimming reading techniques can increase reading motivation in students in e-learning. This research uses the library study method (Library Research). The data was compiled by reading 10 literature research articles related to Skimming. It was found that by applying the use of skimming reading techniques to students ranging from elementary, junior high to students were proven to be able to improve reading skills and analyze the content of the reading subject quickly. Where with the increase in reading skills a learner can be a motivation booster in reading.